On a Pointwise Convergence of Quasi-Periodic-Rational Trigonometric Interpolation. (3rd April 2014) - Poghosyan, Arnak; Poghosyan, Lusine
Abstract : We introduce a procedure for convergence acceleration of the quasi-periodic trigonometric interpolation by application of rational corrections which leads to quasi-periodic-rational trigonometric interpolation. Rational corrections contain unknown parameters whose determination is important for realization of interpolation. We investigate the pointwise convergence of the resultant interpolation for special choice of the unknown parameters and derive the exact constants of the main terms of asymptotic errors.